Hand Hygiene Improvement and Sustainability: Assessing a Breakthrough Collaborative in Western Switzerland. (13th September 2017) - Staines, Anthony; Amherdt, Isabelle; Lécureux, Estelle; Petignat, Christiane; Eggimann, Philippe; Schwab, Marcos; Pittet, Didier
Abstract : OBJECTIVE: To assess hand hygiene improvement and sustainability associated with a Breakthrough Collaborative. DESIGN: Multicenter analysis of hand hygiene compliance through direct observation by trained observers. SETTING: A total of 5 publicly funded hospitals in 14 locations, with a total of 1, 152 beds, in the County of Vaud, Switzerland. PARTICIPANTS: Clinical staff. INTERVENTIONS: In total, 59, 272 opportunities for hand hygiene were monitored for the duration of the study, for an average of 5, 921 per audit (range, 5, 449–6, 852). An 18-month Hand Hygiene Breakthrough Collaborative was conducted to implement the WHO multimodal promotional strategy including improved access to alcohol-based hand rub, education, performance measurement and feedback, reminders and communication, leadership engagement, and safety culture. RESULTS: Overall hand hygiene compliance improved from 61.9% to 88.3% ( P <.001) over 18 months and was sustained at 88.9% ( P =.248) 12 months after the intervention. Hand hygiene compliance among physicians increased from 62% to 85% ( P <.001) and finally 86% at follow-up ( P =.492); for nursing staff, compliance improved from 64% to 90% ( P <.001) and finally 90% at follow-up ( P =.464); for physiotherapists compliance improved from 50% to 90% ( P <.001) and finally 91% at follow-up ( P =.619); for X-ray technicians compliance improved from 45% to 80% ( P <.001) and finally 81% at follow-up ( P =.686). Hand hygiene compliance also significantly increased with sustained improvement across all hand hygiene indications and all hospitals. CONCLUSIONS: A rigorously conducted multicenter project combining the Breakthrough Collaborative method for its structure and the WHO multimodal strategy for content and measurement was associated with significant and substantial improvement in compliance across all professions, all hand hygiene indications, and all participating hospitals. Infect Control Hosp Epidemiol 2017;38:1420–1427